Xenobiotics in the soil environment : monitoring, toxicity and management - Hashmi, Muhammad Zaffar; Kumar, Vivek (Associate Professor); Varma, A. 1939- (Springer, 2017)
This book describes the vast variety of xenobiotics, such as pesticides, antibiotics, antibiotic resistance genes, agrochemicals and other pollutants, their interactions with the soil environment, and the currently available strategies and techniques for soil decontamination and bioremediation. Topics covered include: transport mechanisms of pollutants along the Himalayas; use of earthworms in biomonitoring; metagenomic strategies for assessing contaminated sites; xenobiotics in the food chain; phyto-chemical remediation; biodegradation by fungi; and the use of enzymes and potential microbes in biotransformation. Accordingly, the book offers a valuable guide for scientists in the fields of environmental ecology, soil and food sciences, agriculture, and applied microbiology.- Resumé vydavatel
Includes index.
Keywords: půdní mikrobiologie; xenobiotika; znečištění půdy; soil microbiology; xenobiotics; soil pollution; elektronické knihy; sborníky; electronic books; papers of several authors